Protocol for characterizing community-based rangeland management cases in East Africa and the Sahel - CGIAR Research Program on Livestock (2021)
Protocol has been developed, piloted, and revised and is now guiding case studies at additional sites. UPDATE 2021: Protocol has been published. CGIAR research based on the protocol has been published.